The organisation's core business / Nurzawani Md Sofwan ... [et al.] - Md Sofwan, Nurzawani; Budin, Hemyza; Abd Rashid, Ahmad Faiz; Mohd Anas Khan, Mohd Yazid; Yusuf, Nur Afisha; Abu Bakar, Nur Ain; Emeih Wahed, Wan Juliana; Bohari, Asmah Alia; Morni, Affidah; Johari, Aiza; Perreau, Madeleine Elna (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
The fact that everyone should be able to acquire a solid education reaﬃrms the belief that education is one of the most potent and proven instruments for long-term progress. Sustainable Development Goals (SDG) 2030 is designed to ensure that all girls and boys are given access to a free primary and secondary education. It also intends to ensure that everyone has equal access to inexpensive vocational training, to eliminate gender and economic disparities, and to ensure that everyone gets a decent higher education. UiTM Sarawak is committed in achieving the SDG by doing all in its power to enhance the quality of education it provides, to undertake research with a substantial impact, to manage eﬀective and eﬃcient operations and governance, and to develop its external leadership. Furthermore, the university emphasises on integrating the Sustainable Development Goals and Education for Sustainable Development (ESD) into all its academic programmes, promoting UiTM and national education policies which promote SDG education, and increasing students’ participation in supporting SDG learning as part of their education commitment.